A Study Of The Effectiveness Of Entrepreneurship Education In Fostering Entrepreneurial Mindsets Among Indonesian Youth - Hildianto, Jordi; Iswandari, Ni Komang Priscila Putri (Journal of Business, Management, and Social Studies, 2021)
Objective – This study examines the impact of entrepreneurship education on teenagers’ career aspirations, entrepreneurial mindset, and entrepreneurial intention. Methodology – Using a quantitative method with a cross-sectional design, the study surveyed 200 high school students in Indonesia who had participated in entrepreneurship education programs. The study applied various statistical tests to ensure the reliability and validity of the data and to test the hypotheses. Findings – The results revealed that entrepreneurship education had a positive and significant effect on entrepreneurial intention, but not on entrepreneurial mindset. The study also found that career aspiration did not influence entrepreneurial intention or mindset, but it did affect entrepreneurship education. Novelty – This study focuses on the impact of entrepreneurship education on teenagers in Indonesia. Additionally, the study’s emphasis on the relationship between entrepreneurship education, career aspirations, entrepreneurial mindset, and entrepreneurial intention can be a valuable contribution to the field.